The Dual-Framework AI Maturity Model: Aligning Internal Organisational Readiness with External Product Strategy - Valkama, Oskari (My University, 2026)
Artificial Intelligence (AI) is becoming an integral part of how companies operate, and the fast pace of adoption represents a major strategic shift. Many organisations risk getting stuck in pilot projects rather than turning AI into a real competitive advantage. The core issue is the lack of clear alignment between internal capabilities and the AI products and services brought to mar- ket. Capabilities do not appear on their own. AI model performance roughly doubles every four to six months, and that pace makes keeping up especially difficult. A review of the existing liter- ature shows that current maturity models treat internal organisational capability and external product or service strategy as disconnected silos. This thesis uses the Design Science Research (DSR) method to develop, evaluate, and refine a Dual-Framework AI Maturity Model that addresses this gap. The resulting framework is grounded in the theory of Socio-Technical Systems and in the perspective of dynamic capabili- ties. The dimensions of this newly built maturity framework are based on a structured compar- ative review of seven other maturity models already in established use, combined with the au- thor’s own practitioner experience from working in the research and development function of a Nordic SaaS company that has deployed AI capabilities in production for over 400 enterprise customers, with security and data governance designed into the system architecture. The first version of the framework was validated through semi-structured interviews with seven cross- functional industry experts. The model was then updated based on those interviews to serve the real needs of business even better. The study confirmed that successful AI adoption is held back more by organisational and psy- chological factors than by the technology itself. The theme-based analysis carried out in this study brought to light the need for several structural changes to the model. The findings high- lighted for example the critical need to act according to the rules and regulations set by the EU for data management and security and the end-user resistance to sudden zero-UI agentic inter- faces changes. The resulting Dual-Framework provides organisational leaders with a practical diagnostic tool for strategic planning. It links an organisation’s internal operational readiness with the capability to produce external AI-based products and services. With this two-dimensional view, leadership can identify areas where AI strategy and its execution are out of balance and plan an executable path toward the target state. Despite the interviews, the scope of this study remains limited. Due to that limitation, the model can be considered a theoretical proposition. The next research step is to test and validate further the resulting maturity model with a larger sample of organi- sations.

Tekoälyn nopea käyttöönotto merkitsee suurta strategista muutosta nykyaikaisille yrityksille, mutta monet organisaatiot jäävät jumiin niin sanottuun pilottikiirastuleen. Tämä johtuu siitä, ettei yrityksen sisäisen valmiuden sekä markkinoille tuotavien tekoälytuotteiden ja -palveluiden välillä ole selkeää linjausta. Tekoälymallien suorituskyky noin kaksinkertaistuu 4–6 kuukauden välein, ja tämä kiivas kehitystahti tekee mukana pysymisestä poikkeuksellisen haastavaa. Ole- massa olevan kirjallisuuden tarkastelu osoittaa, että nykyiset kypsyysmallit käsittelevät sisäistä organisaatiokyvykkyyttä ja ulkoista tuotestrategiaa toisistaan erillisinä siiloina. Tämän puutteen ratkaisemiseksi tutkielmassa kehitetään, arvioidaan ja jalostetaan uutta tekoälyn kypsyysmallia Design Science Research -lähestymistavan (DSR) avulla. Kehitetty malli perustuu sosioteknisten järjestelmien teoriaan sekä dynaamisten kyvykkyyksien näkökulmaan, ja sen ulottuvuudet on johdettu seitsemän vakiintuneen kypsyysmallin jäsennellystä vertailusta. Alkuperäinen rakenne pohjautuu kirjoittajan käytännön kokemukseen pohjoismaisen SaaS-yri- tyksen tutkimus- ja kehitysyksiköstä, jossa hän on vastannut yli 400 yritystason tekoälytoime- ksiannosta. Näissä järjestelmissä tietoturva ja datan hallintatapa on suunniteltu suoraan osaksi järjestelmäarkkitehtuuria. Kehystä arvioitiin lopuksi haastattelemalla seitsemää monitoimi- alaista asiantuntijaa puolistrukturoidusti. Arviointi vahvisti, että tekoälyn onnistunutta käyttöönottoa rajoittavat enemmän organisaatio- tekijät ja psykologiset tekijät kuin itse teknologia. Temaattinen analyysi johti useisiin rakenteel- lisiin muutoksiin mallissa. Se toi esiin tietohallinnon perustavan roolin EU:n tekoälyasetuksen kaltaisen sääntelyn puitteissa sekä loppukäyttäjien vastustuksen äkillisiä, käyttöliittymättömiä agenttirajapintoja (zero-UI) kohtaan. Tämän muutosvastarinnan taustalla vaikuttaa usein huoli oman työpaikan kohtalosta. Lisäksi analyysi osoitti tarpeen määrittää konkreettiset, narratiiviset persoonat kuvaamaan kutakin kypsyystasoa. Lopullinen kaksoiskehys tarjoaa organisaation johdolle diagnostisen työkalun, joka yhdistää sisäisen operatiivisen valmiuden ulkoiseen tuotekypsyyteen. Kun nämä kaksi ulottuvuutta asetetaan rinnakkain, johtajat voivat tunnistaa strategisia epätasapainoja. Tästä esimerkkinä on niin sanottu Vaporware-riski, jossa korkean tason tuotetta yritetään rakentaa liian heikon sisäisen perustan päälle. Kehys esitetään teoreettisena väittämänä, ja seuraavassa tutkimusvai- heessa näitä keskinäisriippuvuuksia on tarkoitus testata määrällisellä tutkimuksella laajemman organisaatiootoksen avulla.
Keywords: leadership (activity); enterprises; organisations (systems); development (active); strategies; self-evaluation; strategic leadership; quality awards; quality management; artificial intelligence; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development